Determination of calcium, magnesium, and aluminum in red spruce (Picea rubens) foliage and surrounding soil from the Great Smoky Mountains National Park, Blue Ridge Parkway, and Mount Mitchell State Park using inductively coupled plasma optical emission spectrometry - Rosenberg, Matthew B. (2010)
Red spruce (Picea rubens) trees are medium size conifers found in the Appalachian Mountains at high elevations (above 4500 ft.). Since the 1970’s, several reports indicate a decline of spruce-fir forests in the Southern Appalachian Mountains caused by acid deposition. Acid deposition leaches essential nutrients out of the soil, such as calcium (Ca2+) and magnesium (Mg2+) cations, and increases the availability of toxic metals to plants, such as aluminum cations (Al3+). Investigation of acid deposition effects on red spruce forests was achieved by analyzing calcium, magnesium, and aluminum in foliage and soils of these forests. Samples were collected from various locations on the Blue Ridge Parkway (NC), within the Great Smoky Mountains National Park (NC/TN) and Mt. Mitchell State Park (NC). Foliar and soil samples were collected from 30 red spruce trees (each consisted of 10 matures, 10 saplings, and 10 seedlings,) at each sample site. The concentrations of calcium, magnesium, and aluminum in the foliage and surrounding soils of red spruce trees were determined by using an acid digestion and cation exchange method, respectively. Foliar and soil samples were analyzed using Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES). Statistical (Student's t – test, analysis of variance, and linear regression analysis) and geospatial analysis were performed on the results. There was some correlation in nutrient or toxic metal concentrations found in the foliage or surrounding soils of red spruce trees with respect to elevation of red spruce forests located in the Southern Appalachian Mountains. In spite of the proximity of coal burning power plants located in eastern Tennessee, the majority of western samples sites did not exhibit lower nutrient and higher toxic metal concentrations when compared to eastern sample sites. Inconclusive evidence suggested that soil pH did not influence the nutrient or toxic metal concentrations found in the foliage or surrounding soils of red spruce forests. When foliar nutrient or toxic metal concentrations from red spruce trees were investigated as a function of soil metal concentrations, the majority of the results did not follow the hypothesis that the concentration of nutrients or toxic metals found in the surrounding soils of red spruce trees would correlate with the quantity found within the red spruce tree's foliage. The majority of the results indicated that foliar or soil metal concentrations in mature red spruce, red spruce saplings, and red spruce seedlings were not significantly different. Soil calcium/aluminum molar ratios taken from red spruce trees located in the Southern Appalachian Mountains suggested that almost all sample sites are at high risk of adverse forests health effects. A comparison of previous studies of foliar calcium/aluminum ratios taken from red spruce saplings located at Clingman’s Dome, NC/TN suggested a possible improvement, since in the 1980's, in red spruce forest health. A comparison with previous studies, which spanned 40 years, at Richland Balsam, NC of foliar calcium and magnesium concentrations taken from saplings red spruce trees, suggested a possible improvement in red spruce health at that site since 1994.